English english: english - Prameswari Putri Pratiwi; Relya Crystabella Langoy; Reno Sandyka Rinaldy; Rangga Putra Abu Bakrin (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2025)
ABSTRACT Prambanan Temple, as a world cultural heritage site, has great potential for the development of inclusive tourism. However, accessibility for people with disabilities in this area still faces various obstacles, both physical and non-physical. This study aims to analyze accessibility needs that support inclusive tourism at Prambanan Temple using a qualitative approach through field observations, interviews, and literature reviews. The results indicate that while basic facilities such as ramps, adaptive toilets, audio guides, and mobile apps are available, not all areas of the temple are optimally accessible to people with disabilities. Limitations such as access to the temple courtyard, lack of tactile and visual information, and insufficient staff training are the main barriers. Through comparative analysis with international destinations like the Sydney Opera House and Angkor Wat, it was found that strengthening policies, applying universal design principles, and involving the disability community are key to the success of inclusive tourism. Strategic recommendations include developing adaptive infrastructure, improving accessible information services, and training staff to be responsive to the needs of visitors with disabilities. This research is expected to serve as an empirical foundation for realizing Prambanan Temple as an inclusive and socially just cultural destination. Keywords: accessibility, people with disabilities, inclusive tourism, Prambanan Temple